O protagonismo dos organismos internacionais (PISA) na gestão educacional brasileira diante das avaliações em larga escala - Silveira, Carmem Lúcia Albrecht da (2021)
This work aimed to identify which are the actions that evidence the protagonism of international organizations in the Brazilian educational management disclosed in media documents, aiming to meet the demands of the results of the editions of the International Student Assessment Program (PISA). The research was carried out motivated by the following guiding question: What are the actions that evidence the protagonism of international organizations in Brazilian educational management disseminated through the media and guided by the results of PISA editions? The thesis defended is that with each edition of the dissemination of PISA results, the media documents are responsible for highlighting the role of international organizations in educational management regarding the production and dissemination of educational policies in Brazil. This research was based on the qualitative-quantitative approach, of a bibliographic and documentary nature, constituted based on the theoretical design of pluralism. The methodological procedures consisted in the analysis of the documents published through the media and that structured the aim of study. The categorization of the document analysis of the corpus of the objects of study, composed by national PISA reports and journalistic textual genres, was delimited by conceptual units inventoried from the reading of the objects listed, namely: accessibility (inclusion and democratization of access); performance and quality of national education; literacy and literacy; school failure; school curriculum and the National Curricular Common Base (BNCC); training, appreciation and accountability of teachers; school structure and educational funding; national policies and projects. The time frame deduced by the capture of the objects of study and the legal documents, evidenced that the actions disseminated by the national educational management, delimited the period that began in the 1990s and lasted until the year 2021. authors such as Licínio C. Lima (2017, 2013, 2002, 1997, 1996, 1991a, 1991b), Almerindo J. Afonso (2007a, 2007b, 2001a, 2001b, 1999), Luiz C. Freitas (2018, 2016, 2014, 2012, 2010) and Dalila A. Oliveira (2020, 2017), among others. The analysis of the media documents enabled to locate the representativeness of 57 actions of the national educational management in the delimited period. At the end of the study, it was possible to conclude that the media documents evidenced actions of the national educational management at the macro level, by promoting and elaborating policies that met an established correlation, directly or indirectly, with the guidelines disseminated by the OECD educational agenda.